The rise and fall of the Victorian three-volume novel - Bassett, Troy J. (palgrave macmillan, 2020)
Utilizing recent developments in book history and digital humanities, this book offers a cultural, economic, and literary history of the Victorian three-volume novel, the prestige format for the British novel during much of the nineteenth century. With the publication of Walter Scotts popular novels in the 1820s, the three-volume novel became the standard format for new fiction aimed at middle-class audiences through the support of circulating libraries. Following a quantitative analysis examining who wrote and published these novels, the book investigates the success of publisher Richard Bentley in producing three-volume novels, the experiences of the W. H. Smith circulating library in distributing them, the difficulties of authors such as Robert Louis Stevenson and George Moore in writing them, and the resistance of new publishers such as Arrowsmith and Unwin to publishing them. Rather than faltering, the three-volume novel stubbornly endured until its abandonment in the 1890s. Troy J. Bassett is Professor of English at Purdue University Fort Wayne, USA. He has published numerous articles and book chapters on Victorian book history and literature and is the creator of the digital humanities project At the Circulating Library: A Database of Victorian Fiction, 18371901
Keywords: Geschichte 1820-1900; BooksHistory; Literature, Modern19th century; Great BritainHistory; Literarisches Leben; Roman; Englisch; History of the Book / http://scigraph.springernature.com/things/product-market-codes/814000; Nineteenth-Century Literature / http://scigraph.springernature.com/things/product-market-codes/821000; History of Britain and Ireland / http://scigraph.springernature.com/things/product-market-codes/717020